2018
DOI: 10.2174/2210676608666180119165731
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Narcissism in Adolescents: Relationships with Childhood Maltreatment and Internalizing and Externalizing Difficulties

Abstract: Background: There are significant gaps in our understanding of vulnerable and grandiose narcissism in adolescents and whether it is associated with psychosocial difficulties as well as risk factors such as child maltreatment. Objective: The aim of this study was to examine vulnerable and grandiose narcissism in adolescents and young adults. Method: 570 participants (ages 14-21) from the community completed an online survey. Vulnerable and grandiose narcissism were assessed with the Pathological Narcissism Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Although this approach is supported by previous work in this area (Alexander, 2011; Martinez-Torteya et al, 2014), it decreases the ability to generalize our findings. Indeed, previous findings suggest that childhood abuse is related to both types of narcissism in females, while childhood abuse is not related to either of the types in males (Ensink et al, 2018). In addition to gender, the current sample might have some special characteristics such as the military service mandatory for all Israeli including women, religion-related aspects of education, or the high percentage of individuals living in urban areas that might further limit the generalizability of the present findings to other populations.…”
Section: Resultsmentioning
confidence: 92%
“…Although this approach is supported by previous work in this area (Alexander, 2011; Martinez-Torteya et al, 2014), it decreases the ability to generalize our findings. Indeed, previous findings suggest that childhood abuse is related to both types of narcissism in females, while childhood abuse is not related to either of the types in males (Ensink et al, 2018). In addition to gender, the current sample might have some special characteristics such as the military service mandatory for all Israeli including women, religion-related aspects of education, or the high percentage of individuals living in urban areas that might further limit the generalizability of the present findings to other populations.…”
Section: Resultsmentioning
confidence: 92%
“…For example, in a sample of college students, Ménard and Pincus (2014) reported a nonsignificant correlation between child physical abuse and vulnerable narcissism in female students. However, in a community sample of females aged 14 to 21 years old, Ensink et al (2017) found a moderate and significant positive association between child maltreatment and vulnerable narcissism. Similar patterns are observed on the association between child maltreatment victimization and grandiose narcissism.…”
mentioning
confidence: 74%
“…Of particular interest to the current study is the finding that child maltreatment predicts adult narcissistic traits (Talmon & Ginzburg, 2019). Although a growing body of research has investigated the association between child maltreatment victimization and narcissism (e.g., Bertele et al, 2022; Ensink et al, 2017; Keene & Epps, 2016), research findings varied considerably across studies, suggesting a need to synthesize the findings to obtain a better insight into this association. Therefore, the aim of the current study was to conduct such a quantitative synthesis.…”
mentioning
confidence: 99%
“…Findings for parental care and childhood maltreatment in relation to narcissism have been mixed in previous studies (see e.g. [25,27,29,[74][75][76]). The role of care and childhood maltreatment may therefore be more nuanced.…”
Section: Parental Care and Childhood Maltreatmentmentioning
confidence: 84%